1996
DOI: 10.1089/hum.1996.7.1-51
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Variables Affecting the Efficiency and Efficacy of Adenovirus-Mediated Gene Transfer to Cystic Fibrosis Airway Epithelia

Abstract: Primary cultures of airway epithelia were used to evaluate variables pertinent to adenovirus (Ad)-mediated gene transfer efficiency and efficacy including: (i) Ad-vectors with different promoters, (ii) the duration of vector incubation with cells, (iii) the concentration and depth of vector-containing medium at constant multiplicity of infection (moi) (10(3)), and (iv) the relative sensitivity of reverse transcription polymerase chain reaction (RT-PCR) versus functional analysis for the detection of transduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…We used an adenovirus in which the very strong CMV promoter drove the CFTR cDNA (51) and delivered it to the basolateral surface of well-differentiated non-CF airway epithelia. Our earlier work as well as that of others showed that this procedure produced apically localized and functional CFTR in CF epithelia (17,42). Three days later, we measured transepithelial Cl Ϫ current under short-circuit conditions (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…We used an adenovirus in which the very strong CMV promoter drove the CFTR cDNA (51) and delivered it to the basolateral surface of well-differentiated non-CF airway epithelia. Our earlier work as well as that of others showed that this procedure produced apically localized and functional CFTR in CF epithelia (17,42). Three days later, we measured transepithelial Cl Ϫ current under short-circuit conditions (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…20 8,33 Variation in vector MOI, vector promoters, concentration of vector-containing medium and the duration of vector incubation time are known to affect the transfection efficiency of adenovrial vectors in several cell types. 34,35 Therefore, as a first attempt, we sought to optimize the transfection conditions of human islets with Adv-GFP-hVEGF. The GFP intensity of islets after transfection with Adv-GFP-hVEGF increased with increase in MOI from 50 to 5000 (Figure 2), suggesting efficient transfection at high MOI.…”
Section: Discussionmentioning
confidence: 99%
“…As has been reported in other human studies to improve CFTR function or to transfer cftr to CF-affected tissues, Na ϩ transport as measured by the nasal PD was unaffected by gentamicin treatment (Figures 4 and 5). This may reflect the higher sensitivity of measurable Cl Ϫ secretion in the context of low-level CFTR activity, compared with attenuation of Na ϩ hyperabsorption (15,24,30,(32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%